x ^ a * x ^ b = x ^ ( a + b )
2 ^ 2 * 2 ^ 8 = 2 ^ ( 2 + 8 ) = 2 ^ 10
( 2.5 * 10 ^ 4 )( 4 * 10 ^ 3 ) = 2.5 * 4 * 10 ^ ( 4 + 3 ) = 10 * 10 ^ 7 = 10 ^ 1 * 10 ^ 7 = 10 ^ ( 1 + 7 ) = 10 ^ 8
Write the expression using a single exponent.
2^2 * 2^8
A. 4^10
B. 2^10
C. 4^16
D. 2^16
Write the expression using scientific notation.
(2.5 * 10^4)(4 * 10^3
A. 10 * 10^7
B. 10 * 10^8
C. 1 * 10^8
D. 10 * 10^12
3 answers
Bosnian is right guys-
To be clear:
2^2 + 2^8
B. 2^10
(2.5 * 10^4)(4 * 10^3)
C. 1 * 10^8
2^2 + 2^8
B. 2^10
(2.5 * 10^4)(4 * 10^3)
C. 1 * 10^8